ERUPTION CYST OVERLYING THE CROWN OF UPPER RIGHT FIRST PREMOLAR: A CASE REPORT: KISTA ERUPSI YANG MENUTUPI MAHKOTA PREMOLAR PERTAMA KANAN ATAS: LAPORAN KASUS - Wayan Sutresna Yasa; Kirana Guspiari; I Made Hendra Cahyadita Nusantara Putra (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: An eruption cyst is one of the odontogenic cyst involving the soft tissue, associated with the eruption of the primary or permanent tooth that lies behind the cyst. It often occurs in children; first permanent molars and maxillary incisors are the most prevalent teeth. Case: This article report an eruption cyst case in a 9-year-old female patient. The patient came with swelling on the gingiva overlying the crown of 14, and , clinically, the tooth has not erupted yet. Intraoral examination revealed the presence of smooth swelling, 1 cm x 0.8 cm, with bluish-black color. Case Management: Surgical incision under local anesthesia was performed to remove the cyst and exposed the tooth. Discussion: Eruption cyst is a soft tissue cyst. The exact aetiology remains unclear. It appears as a dome-shaped swelling, soft, transparent, bluish to blue-black color. It’s hard to distinguish eruption cyst on radiograph examination, because it’s a soft tissue cyst, no bone involvement. Histologically, it presents connective tissue covered with layer of non-keratinized squamous epithelium. A small asymptomatic eruption cyst does not require any treatment because it could rupture spontaneously. If it causes a problem, it must be removed by incision and drainage the cyst fluid contents. In this case, the cyst treated with simple incision, the tooth was exposed and could erupt normally. Conclusion: The latest knowledge and developments in diagnosis and treatment of eruption cysts are important for clinicians to understand in order to decide the right diagnosis and treatment plan.